Diversifikasi Konten Tonight Show dan Regulasi yang Berlaku Pada Media Massa (NET TV) dan Media Online (Youtube) - Jasmin Jannatania; Eni Maryani; Dadang R Hidayat; Sri S Indriani (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2022)
The Tonight Show is a talk show program that has been broadcast on NET TV since 2013. Recently, NET TV made a new strategy for the Tonight Show program by creating a new program that is only broadcast on the Youtube platform only. The purpose of this study is to explain the content diversification strategy carried out by NET TV using Mosco's political economy theory, with a descriptive comparative study method. This study also compares the regulation of television media with Youtube media when one program is broadcast on two different platforms, which also have very different content. The findings of this study are that NET TV's strategy to diversify content is quite successful, as seen from the high subscriber of the TonightShowNET Youtube channel when the Tonight Show Premiere was first broadcast, and the number of viewers who continued to rise when the special was uploaded. Another finding is that Youtube already has regulations for users and creators who do violate the rules, but when compared to P3SPS which has been compiled by KPI, the viewing standards on Youtube are still not appropriate.